Active fault tolerant control of nonlinear systems: the cart-pole example - Bonfé, Marcello; Castaldi, Paolo; Mimmo, Nicola; Simani, Silvio (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes the design of fault diagnosis and active fault tolerant control schemes that can be developed for nonlinear systems. The methodology is based on a fault detection and diagnosis procedure relying on adaptive filters designed via the nonlinear geometric approach, which allows obtaining the disturbance de-coupling property. The controller reconfiguration exploits directly the on-line estimate of the fault signal.
Keywords: fault detection and isolation; nonlinear filter; nonlinear geometric approach; fault-tolerant control; cart-pole nonlinear model